Enhancing Health Service Efficiency through the Implementation of Electronic Medical Records: A Health Management Perspective - Winphy Prasetyo; Sri Sundari (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Electronic Medical Records (EMRs) are digital records that enhance healthcare efficiency by reducing waiting times, improving coordination, minimizing errors, and accelerating diagnosis. This study aims to assess the efficiency of service times for hypertension patients through the adoption of EMRs. A quantitative observational design was employed, utilizing probability sampling (random) with the Slovin formula, yielding a sample size of 347 patients. Data was collected using an observation sheet during service encounters, and bivariate analysis was performed using the Paired Sample t-Test in SPSS version 30.0. Before the t-test, normality tests were conducted to ensure the data followed a normal distribution. If the data were found to be abnormal, the Wilcoxon Signed-Rank Test was applied as an alternative non-parametric test. The total service time for 347 patients using the EMR system was 271,438 seconds, while the manual system recorded a total of 666,798 seconds. On average, the service time per patient using EMRs was 782 seconds (13.02 minutes), compared to 2,248 seconds (37.46 minutes) for the manual system. The findings demonstrate that the EMR system significantly improves service time efficiency, highlighting its potential to enhance the effectiveness and timeliness of healthcare delivery.   Keywords: Digital Transformation, Electronic Medical Records (EMR), Health Services, Time Efficiency, Health Technology.